(untitled) (Journal of Mechanical Engineering, 2015)
This article finds the relationship of Inventory management with industries becoming sick. Inventory planning and control are of special importance to sales, production, and finance of any firm. Proper inventory management gives an idea of relationship between raw material, work-in-process and finished goods or consumption of finished goods. From the collected data it is clear that many local plants have either no fixed norm(s) or do not practice proper way of controlling the inventory. This might be the case in many third world countries. In this article it has been discussed how to overcome sickness of industries by controlling and standardizing inventory planning and control. Also how productivity and firms financial conditions are affected by proper inventory management has also been discussed in this article.